2019
DOI: 10.1002/jclp.22833
|View full text |Cite
|
Sign up to set email alerts
|

PTSD from a suicide attempt: An empirical investigation among suicide attempt survivors

Abstract: Objectives Suicide attempts (SAs), by definition, represent a risk for serious injury or death; thus, one's SA may contribute to the development of posttraumatic stress disorder (PTSD). Yet, empirical data on this topic are lacking. This study aimed to characterize the phenomenology, rate, and associated features of PTSD following one's SA. Method A total of 386 adult SA survivors recruited from web‐based sources participated. Results Overall, 27.5% (95% confidence interval = 23.1–31.9%) of SA survivors screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
(96 reference statements)
2
17
0
Order By: Relevance
“…This is in accordance with studies finding an increased risk of development of PTSD after trauma in persons with preexisting major depressive disorder (Breslau, Davis, Peterson, & Schultz, 1997; Digangi et al, 2013). Other known PTSD risk factors, such as gender (Brewin et al, 2000), did not predict PTSD in our study, which is in accordance with the study by Stanley, Hom et al (2019). Whether these results are false negatives due to small sample sizes or whether known risk factors for PTSD in general do not apply to saPTSD must be answered by future studies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is in accordance with studies finding an increased risk of development of PTSD after trauma in persons with preexisting major depressive disorder (Breslau, Davis, Peterson, & Schultz, 1997; Digangi et al, 2013). Other known PTSD risk factors, such as gender (Brewin et al, 2000), did not predict PTSD in our study, which is in accordance with the study by Stanley, Hom et al (2019). Whether these results are false negatives due to small sample sizes or whether known risk factors for PTSD in general do not apply to saPTSD must be answered by future studies.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, nearly half of the patients after DWI with suicidal intention had probable PTSD at the time of follow‐up. Stanley, Hom et al (2019), and Bill et al (2012) found similar rates of suicide attempt‐associated PTSD (saPTSD, 27.5% and 46.7%), speaking to the validity of our findings. Thus, traumatization in the context of a suicide attempt may be a hitherto unknown risk factor for PTSD (OR = 14.0).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations